Carbon monoxide intoxication: What we know. Issue 3 (May 2019) - Reumuth, Georg; Alharbi, Ziyad; Houschyar, Khosrow Siamak; Kim, Bong-Sung; Siemers, Frank; Fuchs, Paul Christian; Grieb, Gerrit
Abstract: Carbon monoxide (CO) is a toxic, color-, taste- and odorless gas with fatal consequences if undetected. Intoxication caused by CO is frequent possibly leading to a high morbidity and mortality. The disease involves multiple organ systems without a typical clinical presentation. The clinical picture is furthermore unrelated to levels of carboxyhemoglobin — the routine biomarker. Therefore the diagnosis and treatment can be very demanding. This article in detail reviews epidemiology, symptoms, diagnosis and the therapy of this multidisciplinary challenge.